Enhanced surface free energy of UHMWPE fibers and its interfacial adhesion behavior to PI resins. (12th January 2018) - He, Runqin; Chang, Qiuxiang; Huang, Xinjun; Li, Jian
Abstract : Mechanical properties of composites made up of ultra‐high‐molecular‐weight polyethylene (UHMWPE) fiber, polyimide (PI), and TiO2 particles were investigated. The hybrid composite of 20 vol% of UHMWPE fiber with TiO2 showed tensile strength greater than UHMWPE fiber/PI composite. A positive hybrid effect in tensile strength is obtained. It is observed that addition of small amount of TiO2 to UHMWPE fiber/PI increased the tensile strength of the composite by 28%. With increase in TiO2 loading to 1 to 3 vol%, the impact strength of the hybrid composite is increased from 55 KJ/m 2 to 69 KJ/m 2 . This maximum value is more than one and a half times greater than the impact strength of neat UHMWPE fiber/PI composite.